Cultivation of Gardenia jasminoides shoots in temporary immersion systems and optimization of the immersion periods - Krasteva Gergana (BIO Web of Conferences, 2023)
In the present study, the effect of different immersion regimes on the growth and secondary metabolites production by shoot cultures of Gardenia jasminoides Ellis, cultivated in temporary immersion systems (TIS) was investigated. The cultivation was performed for 30 days on MS medium supplemented with 4.0 mg/L BAP. The regimes of cultivation included 15 min. immersion every 4, 8 and 12 hours. The highest amount of accumulated dry biomass (ADB = 10.86 ± 0.02 g/L) was reached at 15 min. immersion at every 8 hours, whereas the lowest (ADB = 4.65 ± 0.26 g/L) was recorded when 15 min. immersion on every 4 hours was used. HPLC analyses showed that the higher polyphenol content was achieved when shoots were cultivated by using 15 min. immersion on every 12 hours. At this conditions, the shoots produced maximal amounts of chlorogenic acid (164.82±32.36ug/g DW), caffeic acid (26,90±6,80μg/g DW), rutin (891,67±122,29μg/g DW) and rosmarinic acid (559,19±19,85μg/g DW). The observed antioxidant activity (DPPH, ABTS, CUPRAC and FRAP) was following the accumulation of total phenolic. The study demonstrates that TIS are effective for cultivation of Gardenia jasminoides shoots.